ANALISIS KEBUTUHAN IRIGASI LAHAN PERTANIAN KANAL PORONG DI KABUPATEN SIDOARJO MENGGUNAKAN CROPWAT 8.0 - Nur Afifah Anshori; Siti Sarah Rodhiah Mariza; Titah Indit Pakarti; Ferryati Masitoh; Fajar Setiawan Yuliano (Universitas Negeri Padang, 2022)
Porong Canal is one of the irrigation network systems originating from the Lengkong Baru Weir which flows an irrigation area of 11,059 hectares in the Brantas Hilir Subwatershed. The need for irrigation in planting is very important because it is related to the availability of water and local climatic conditions. For this reason, research on cropping patterns and water requirements was carried out using the Cropwat software. Based on the research results, the Porong Canal irrigation area may have a rice-rice-corn cropping pattern. The total water requirement of plants at planting period 1 (paddy) was 562.4 mm thick, planting period 2 (rice) was 200.6 mm thick, and planting period 3 (corn) was 431.4 mm thick. Based on the water requirement, a irrigation plan is carried out every ten days with a total thickness of irrigation at the planting period of 1 thick (400.9 mm), planting period 2 (146 mm), and planting period 3 (276 mm). Provision of irrigation water every decade of the day is different depending on the growth phase. Total irrigation is different for each planting due to seasonal factors (rainfall), evapotranspiration, soil physical properties and crop coefficients.